ISSUES OF TOURISM DEVELOPMENT IN UZBEKISTAN (BASED ON FOREIGN EXPERIENCES) - Mukhlisa Bakhtiyorova (Bright Mind Publishing, 2025)
The article presents an analysis of the studied foreign experience, acquired theoretical knowledge, as well as a number of regulatory documents.
Keywords: Tourism, methodology, tourist, transport, social, income, socio-economic, resource, hostel, traditions.